Cellular delivery of dinucleotides by conjugation with small molecules: targeting translation initiation for anticancer applications. Issue 30 (6th July 2021) - Kleczewska, Natalia; Sikorski, Pawel J.; Warminska, Zofia; Markiewicz, Lukasz; Kasprzyk, Renata; Baran, Natalia; Kwapiszewska, Karina; Karpinska, Aneta; Michalski, Jaroslaw; Holyst, Robert; Kowalska, Joanna; Jemielity, Jacek
Abstract : Ligand assisted cellular delivery of negatively charged dinucleotides, which are potential antagonists of the protooncogenic protein eIF4E. Abstract : Targeting cap-dependent translation initiation is one of the experimental approaches that could lead to the development of novel anti-cancer therapies. Synthetic dinucleoside 5′, 5′-triphosphates cap analogs are potent antagonists of eukaryotic translation initiation factor 4E (eIF4E) in vitro and could counteract elevated levels of eIF4E in cancer cells; however, transformation of these compounds into therapeutic agents remains challenging – they do not easily penetrate into cells and are susceptible to enzymatic cleavage. Here, we tested the potential of several small molecule ligands – folic acid, biotin, glucose, and cholesterol – to deliver both hydrolyzable and cleavage-resistant cap analogs into cells. A broad structure–activity relationship (SAR) study using model fluorescent probes and cap–ligand conjugates showed that cholesterol greatly facilitates uptake of cap analogs without disturbing the interactions with eIF4E. The most potent cholesterol conjugate identified showed apoptosis-mediated cytotoxicity towards cancer cells.